FORMATION OF FOREIGN LANGUAGE COMPETENCE AT THE PROFESSIONAL GROWTH OF TECHNICAL AND TECHNOLOGICAL SPECIALTIES STUDENTS - Яременко-Гасюк, О. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The paper discusses the importance of the formation of foreign language competence as one of the key problems, the solution of which will contribute to the innovative development of national education. In the same context, we should do the training of students of technical and technological specialties (TTS), which in the future will determine the process of harmonious introduction of our country into the world community. Therefore, as the basis for the reform of technical and technological education, it would be advisable to put the competence and activity (pragmatic) approaches, which, together with the latest information and communication technologies in the information and educational environment context, ensure the effective growth of the student’s personality, not only due to the knowledge gained, but also through the acquisition of own experiences and development of creative thinking. The article provides a model of foreign language competence formation for TTS students in terms of information - educational environment and the characteristics of each of its components. The article noted the importance of introducing a creative component, which is now, in terms of reforming the educational system, should be responsible for the formulating of new ideas and generating new perception of the world in the process of professional development of TTS students